2021
DOI: 10.1111/1471-0307.12777
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐inflammatory and anti‐oxidative potential of synbiotics in two independent cell lines

Abstract: This study was performed to help the researchers who are investigating or screening functional Lactobacillus strains with some kinds of prebiotics such as oligosaccharide, polysaccharide and fibre throughout serial in vitro study. We selected some Lactobacillus strains with prebiotics to be treated on two cell lines that we hypothesised them as gut and brain when the host consumes synergistic synbiotics. Selected synergistic synbiotics candidate significantly protected each cell against different stressors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…Colorectal cancer is the third most diagnosed and represents 10% of all cancer cases (Razali et al, 2016;International Agency for Research on Cancer, 2020). In this study, when HCT-116 was exposed to the C5 fraction at the highest concentration, showed significantly (p ≤ 0.05) low percentages of viability, even lower than in other studies with the same cell line (Rafiq et al, 2020;Eor et al, 2021).…”
Section: Fractionscontrasting
confidence: 78%
“…Colorectal cancer is the third most diagnosed and represents 10% of all cancer cases (Razali et al, 2016;International Agency for Research on Cancer, 2020). In this study, when HCT-116 was exposed to the C5 fraction at the highest concentration, showed significantly (p ≤ 0.05) low percentages of viability, even lower than in other studies with the same cell line (Rafiq et al, 2020;Eor et al, 2021).…”
Section: Fractionscontrasting
confidence: 78%
“…Therefore, antioxidants that scavenge free radicals could have the potential to reduce inflammation Samarghandian et al (2016). the DPPH assay, TP, and TF contents are indicators of the antioxidant potential of a substance (Ghasemzadeh & Jaafar, 2014;Eor et al, 2021). It has been determined that the antioxidant properties of fermented lemon peel are superior to that of unfermented lemon peel in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, studies have shown that combination of prebiotics renders better results on probiotics growth and function (Jakobsen et al ., 2019; Sarfraz et al ., 2019; Eor et al ., 2021; Liu et al ., 2023b). Han reported the synergism between probiotics and prebiotics (Han et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%